Sizing of a Standalone PV System with Battery Storage for a Dairy: A Case Study from Chile. (12th December 2020) - Viveros, Pablo; Wulff, Francisco; Kristjanpoller, Fredy; Nikulin, Christopher; Grubessich, Tomás
Abstract : In this paper, a stochastic simulation model for a standalone PV system sizing is replicated and extended to supply a dairy's power demand. A detailed hourly-based simulation is conducted considering an hourly load profile and global solar radiation prediction model. The stochastic simulation model is based on a thorough statistical analysis of the solar radiation data and simulates the energy yield, the excess energy curtailed, and the state of charge of the batteries for the sizing month and the whole year, providing the designer autonomy factor values d to properly size the PV system, finding the optimum combination of installed peak power P m and battery storage capacity C L that meets the application load requirements, considering a preset reliability level at minimum cost. The model makes use of the NASA'S Surface Meteorology and Solar Energy database to obtain solar radiation data. Results show a substantial reduction of 44% in installed peak power and battery storage capacity when compared to conventional methodologies, considering three days of autonomy, and an 85% reduction considering four days. Considering the goodness of fit test results, the Wakeby distribution best represents the behavior of historical solar radiation data for the site in almost half of the months. This article seeks to contribute to the literature gap in the application of methodologies for the multicomponent power supply in the dairy industry through the use of renewable energy.